Employment of International Students in the South Karelia Region - Korkeila, Annika; Liikanen, Anni (Saimaan ammattikorkeakoulu, 2010)
This thesis “Employment of International Students in the South Karelia Region” was formed around the issue of employment that international students struggle with during their studies and after graduation. Saimaa University of Applied Sciences had noticed the unemployment issue and wanted to find out some answers why students are not employed, as well as whether or not companies were able to offer opportunities in making the situation better for the students and the community as a whole. The main problem appears to be that the students receive a free education in Finland, yet tend to leave the country upon completion of their studies, unable to find work opportunities related to their field of studies that will allow them to pursue a successful and desirable career. This research was conducted by interviewing both international students and local companies. In general, the outlook of the situation was that companies were suffering from the economical crisis and had difficulties in keeping their previous workers employed. Under the crisis also laid the issue that international students do not speak Finnish. Students’ opinions were similar in every faculty in the Saimaa University of Applied Sciences. International students told that finding a job is almost impossible because they do not speak Finnish. The main objective of the interviews was to get to know the topic throughout and possibly have an awakening impact on the people related to the situation. Companies were keen on trying to make the situation better for the students and at the same time they realized they should also appreciate the benefits and advantages the international background of a student can bring. Students defined having a direct contact with personnel managers of the companies as a priority. Opinnäytetyö muodostui ulkomaalaisten opiskelijoiden työllistymisen ympärille Etelä-Karjalan alueella. Työllistyminen on ongelma, jonka kanssa opiskelijat usein kamppailevat opintojensa aikana ja valmistumisen jälkeen. Saimaan ammattikorkeakoulu oli huomannut ongelman jo aiemmin, ja se halusi vastauksia kysymyksiinsä, miksi ulkomaalaisia opiskelijoita ei palkata ja olisiko opiskelijoiden tilanteeseen mitään ratkaisua, joka auttaisi opiskelijoita. Ongelmana on se, että kansainväliset opiskelijat koulutetaan Suomessa, mutta he saattavat joutua lähtemään maasta, koska eivät löydä koulutustaan vastaavia töitä. Tutkimus pohjautui ulkomaalaisten opiskelijoiden ja paikallisten yrityksien haastatteluihin. Tutkimuksen yksi tärkein löydös oli se, että usein yritykset mainitsivat kansainvälisen opiskelijan palkkaamisen esteeksi opiskelijoiden heikon suomen kielen taidon. Eri alojen opiskelijat Saimaan ammattikorkeakoulusta olivat samaa mieltä ongelmasta, työhön pääsy on lähes mahdottomuus, jos ei osaa puhua suomea. Tutkimuksen tarkoitus oli perehtyä aiheeseen syvällisesti ja herätellä yrityksiä tilanteen vakavuudesta. Yritykset olivat kiinnostuneita auttamaan opiskelijoiden tilannetta ja ehkä jopa hyötymään itse opiskelijan kansainvälisestä taustasta. Opiskelijat toivoivat seminaareja, joissa saisivat suoraan kontaktin yrityksiin ja näkyvämpää apua työpaikkojen löytämiseen.